Phytoremediation of water quality in the Ciujung River with local potentials of Panicum sp. Bioagent - Widayati Norwulan; Mahrawi Mahrawi; Gilang Ramadhan; Zahra Ismaya (Biological Environment and Pollution, 2022)
The Ciujung River has been polluted and its load carrying capacity has decreased. Several parameters that exceed water quality standards are BOD, COD, DO, TDS, temperature, and pH. One of the methods that can be used to reduce pollution in Ciujung River water is phytoremediation. Phytoremediation, namely cleaning, eliminating, and reducing toxicity in polluted land or water with photosynthetic plant mediators. This study aims to improve the water quality of the Ciujung River using the phytoremediation method using plants from the Poaceae family, namely Panicum sp. This study used static phytoremediation techniques with plant variations of 300 grams (P1), 500 grams (P2), and 700 grams (P3) in 5 liters of Ciujung River water samples for 30 days. The results showed that for the mass variation of 300 grams (P1), there was an increase in pH from 6-8, an increase in TDS from 97-322.5 ppm, and a decrease in temperature from 29-25.3°C. In the 500 gram mass variation (P2) there was an increase in pH from 6-8, an increase in TDS from 97-460 ppm, and a temperature from 29-25.4°C. In the 700 gram mass variation (P3) there was an increase in pH from 6-8, an increase in TDS from 97-461 ppm, and a decrease in temperature from 29-25.6°C. And there was a decrease in BOD from 15.6 mg/L – 1.2 mg/L, COD from 33.2 mg/L – 10.3 mg/L, and an increase in DO from 3.7 mg/L – 15.7 mg /l.